Differentiating between remote and local strain fields near mesoscale faults by magnetic fabrics in deformed chalks. (February 2022) - Issachar, R.; Levi, T.; Weinberger, R.
Abstract: Characterizing the strain field near faults is a key to understanding its formation origin, kinematics and mechanism. We use magnetic fabrics and Anisotropy of Magnetic Susceptibility (AMS) as strain markers to study the development of the strain field near mesoscale normal faults cutting a weakly deformed chalk host rock that crops out in the Beer Sheva syncline, Israel. We provide a high-resolution view of the magnetic fabrics by constructing horizontal cross-sections, from distance of <0.2 m up to ∼20 m from the fault planes. The results indicate deformation fabrics that are controlled by the orientation-distribution of calcite coccolith in the chalk. The AMS axes indicate similar and consistent orientations at all localities, even though adjacent faults have different orientations, indicating that the strain field did not develop as a result of the slip along the faults. The maximum susceptibility axes (K 1 ) and the intermediate susceptibility axes (K 2 ) axes are parallel and perpendicular to the syncline axis, respectively. These relations suggest that the magnetic fabrics had already been acquired before of the faults and represent the remote strain field that was operating during the formation of the Beer Sheva syncline. We provide independent arguments for an aseismic slip origin of the studied faults, and, by comparing the results with magnetic fabrics near co-seismic faults that formed under similar sedimentary conditions, we highlight the possibility that aseismic and seismic faults have different impact on the distribution of magnetic fabrics and inelastic deformation near them. Highlights: AMS of chalks near meso faults in an open syncline characterize inelastic deformation. Strain near the faults reflects the remote strain field during syncline formation. We highlight the possibility of using AMS to distinguish slip rate histories.